HUBUNGAN PERILAKU CARING PERAWAT DENGAN TINGKAT KEPUASAN PASIEN DI RUMAH SAKIT PERMATA BUNDA MEDAN TAHUN 2019 - Sukma Yunita; Panri Hariadi (STIKes Murni Teguh, 2019)
Quality health services are services that can satisfy every service user, nurses in providing services are manifested in a caring attitude. Nurse caring behavior is one of the determinants of patient satisfaction. This type of research uses descriptive correlation and the design of this study uses a cross sectional design, the population in this study is all patients treated in the emerald II room as many as 420 people. The sampling technique was purposive sampling. Data analysis was performed by univariate and bivariate using chi square tests. The results of the study that the majority of caring behavior is always as many as 37 respondents (88.1%), the majority of patient satisfaction is very satisfied as many as 37 respondents (88.1%). Statistical test results with chi square obtained value of 0.000 <0.05 means that there is a relationship between caring behavior with the level of patient satisfaction at the Permata Bunda General Hospital in 2019. The conclusion of the study is the relationship between caring behavior with the level of patient satisfaction at the Permata Bunda General Hospital 2019. It is recommended for nurses to improve the quality of nursing service delivery of nursing services especially nurses caring behavior with patient satisfaction so that it can improve the quality of nursing services and the quality of the hospital is getting better. Pelayanan kesehatan yang bermutu adalah pelayanan yang dapat memuaskan setiap pemakai jasa layanan, perawat dalam memberikan pelayanan diwujudkan dalam sikap caring. Perilaku caring perawat merupakan salah faktor penentu kepuasan pasien. Jenis penelitian menggunakan deskriptif korelasi dan desain penelitian ini menggunakan desain cross sectional, populasi dalam penelitian ini adalah seluruh pasien yang dirawat di ruang zamrud II inap sebanyak 420 orang. Teknik pengambilan sampel dengan purposive sampling. Analisa data dilakukan dengan univariat dan bivariat menggunakan uji chi square. Hasil penelitian bahwa perilaku caring mayoritas selalu sebanyak 37 responden (88,1 %), kepuasan pasien mayoritas sangat puas sebanyak 37 responden (88,1 %). Hasil uji statistik dengan chi square diperoleh nilai value sebesar 0.000 < 0,05 artinya terdapat Hubungan perilaku caring dengan tingkat kepuasan pasien di Rumah Sakit Umum Permata Bunda tahun 2019. Kesimpulan penelitian terdapat Hubungan perilaku caring dengan tingkat kepuasan pasien di Rumah Sakit Umum Permata Bunda Tahun 2019. Disarankan untuk perawat untuk meningkatkan kualitas dalam pemberian pelayanan keperawatan pemberian pelayanan keperawatan khususnya perilaku caring perawat dengan kepuasan pasien sehingga dapat meningkatkan mutu pelayanan keperawatan serta kualitas Rumah Sakit semakin baik.